A RelA–SpoT homolog (Cr-RSH) identified in Chlamydomonas reinhardtii generates stringent factor in vivo and localizes to chloroplasts in vitro - Kasai, Koji (Oxford University Press, 2002)
A gene encoding a putative guanosine 3′,5′-bispyrophosphate (ppGpp) synthase–degradase, designated Cr-RSH, was identified in the unicellular photosynthetic eukaryote Chlamydomonas reinhardtii. The encoded Cr-RSH protein possesses a putative chloroplast-targeting signal at its NH(2)-terminus, and translocation of Cr-RSH into chloroplasts isolated from C.reinhardtii was demonstrated in vitro. The predicted mature region of Cr-RSH exhibits marked similarity to eubacterial members of the RelA–SpoT family of proteins. Expression of an NH(2)-terminal portion of Cr-RSH containing the putative ppGpp synthase domain in a relA, spoT double mutant of Escherichia coli complemented the growth deficits of the mutant cells. Chromatographic analysis of (32)P-labeled cellular mononucleotides also revealed that expression of Cr-RSH in the mutant bacterial cells resulted in the synthesis of ppGpp. SpoT, which catalyzes (p)ppGpp degradation, is dispensable in E.coli only if cells also lack RelA, which possesses (p)ppGpp synthase activity. The complementation analysis thus indicated that Cr-RSH possesses both ppGpp synthase and degradase activities. These results represent the first demonstration of ppGpp synthase–degradase activities in a eukaryotic organism, and they suggest that eubacterial stringent control mediated by ppGpp has been conserved during evolution of the chloroplast from a photosynthetic bacterial symbiont.